Transformational Style of Leadership and Psychological Capital: The Mediating Role of Work Engagement - Martha Sari Ayu; Bambang Niko Pasla; Fathiyah Fathiyah; Lailatul Isnaini; Novita Erlinda (Jurnal Prajaiswara, 2022)
Introduction/Main Objectives: This study aims to determine the direct effect of psychological capital on organizational citizenship behavior, psychological capital on work engagement, transformational leadership on organizational citizenship behavior, transformational leadership on work engagement, work engagement on organizational citizenship behavior. An indirect effect of psychological capital and transformational leadership on organizational citizenship behavior by mediating work engagement Background Problems: The times are increasingly rapid and dynamic, especially the challenges faced by companies, especially in developing countries, are getting bigger, and an organization must be able to adapt to environmental changes to survive and grow to achieve the goals of the organization, requiring support from internal and external factors that affect the organization to be managed properly and efficiently. Research Methods: The research method used is review of articles and literature studies sourced from journals and books. Finding/Results: The results of the hypothesis that the direct or indirect effect of psychological capital, transformational leadership, and work engagement on organizational citizenship behavior has a positive and significant impact. Conclusion Transformational leadership contributes to increasing employee self-efficacy, hope, resilience, and a sense of optimism. Transformational leadership and psychological capital are independently related to trust in management and impact individual and organizational performance. Still, they can also moderate each other, which will affect climate of an organization and work engagement.